A brighter dawn - Gould, Leslie, 1962- (Amish memories, 2023)
"When Ivy Zimmerman's Mennonite parents are killed in a tragic accident, her way of life is upended. As she grows suspicious that her parents' deaths weren't an accident, she gains courage from her Amish great-grandmother's time in pre-war Germany in 1937. With the inspiration of her great-grandmother, Ivy seeks justice for her parents, her sisters, and herself"--